Influenza and Bacterial Superinfection: Illuminating the Immunologic Mechanisms of Disease - Rynda-Apple, Agnieszka; Robinson, Keven M; Alcorn, John F (Infection and immunity, 2015)
Seasonal influenza virus infection presents a major strain on the health care system. Influenza virus infection has pandemic potential, which was repeatedly observed during the last century. Severe disease may occur in the young, in the elderly, in those with preexisting lung disease, and in previously healthy individuals. A common cause of severe influenza pathogenesis is superinfection with bacterial pathogens, namely, Staphylococcus aureus and Streptococcus pneumoniae. A great deal of recent research has focused on the immune pathways involved in influenza-induced susceptibility to secondary bacterial pneumonia. Both innate and adaptive antibacterial host defenses are impaired in the context of preceding influenza virus infection. The goal of this minireview is to highlight these findings and synthesize these data into a shared central theme of pathogenesis.